Performance evaluation and analysis of 64-quadrature amplitude modulator using Xilinx Spartan FPGA - Anthony Prathap, Joseph; S.Anandhi, T; Ramash Kumar, K; Srikanth, B (International Journal of Engineering and Technology, 2018)
This paper proposes the design of 64-Quadrature Amplitude Modulation using the Very High Speed Integrated Circuit Hardware Description Language (VHDL) coding and XILINX SPARTAN Field Programmable Gate Array (FPGA) real-time implementation for validation. QAM is used in modern digital communication applications like set-top box, satellite TV, wireless and cellular technology etc. In this paper, 64-QAM is implemented and compared with three different XILINX SPARTAN FPGA devices say 3A DSP, 3E and 6E. The power, current and thermal parameters are performed and compared. The power consumed for the design of 64 QAM using the Xilinx SPARTAN 6E FPGA device is 0.014W and 15.9 C/W of Effective TJA for the XILINX SPARTAN 3A DSP FPGA. The device utilization of the 64-QAM design using the XILINX SPARTAN 3A DSP is low.